ANALISIS PERLINDUNGAN HAK PARA PIHAK DALAM IMPLEMENTASI E-COURT DAN E-LITIGATION PADA PERADILAN PERDATA - Anggi Sri Haryati Simarmata; Abd Manaf (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2026)
This study aims to analyze the protection of the parties' rights in the implementation of e-Court and e-Litigation in civil justice in Indonesia. The background of this research is based on the transformation of the judicial system towards digitalization as a response to the development of information technology in the era of the Industrial Revolution 4.0. The research method used is normative juridical with statutory and conceptual approaches, supported by literature studies of primary and secondary legal materials. The results show that the implementation of e-Court and e-Litigation provides convenience in access to justice through efficiency in time, cost, and transparency of judicial processes. However, there are still several challenges in protecting the rights of the parties, such as the digital divide, low digital literacy, and potential violations of fair trial principles, including the right to be heard and the right to defense. In addition, there are risks of abuse of process and issues related to the validity and security of electronic documents